1983
DOI: 10.1017/s0033291700047991
|View full text |Cite
|
Sign up to set email alerts
|

Screening for abnormal eating attitudes and psychiatric morbidity in an unselected population of 15-year-old schoolgirls

Abstract: SynopsisThe Eating Attitudes Test (EAT) and General Health Questionnaire (GHQ) have been validated in an unselected population of 15-year-old South London schoolgirls. Scores on the questionnaires were compared with the results of standard interview. The EAT was found to be an efficient screening instrument for abnormal eating attitudes and behaviour, whereas the GHQ was less satisfactory in its ability to screen for psychiatric morbidity in this age group than in adults. At the optimal cutting points, 6·9% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
7
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(133 citation statements)
references
References 16 publications
12
111
7
3
Order By: Relevance
“…In the present study, the cut-off was 21 points, for this presents highly satisfactory sensitivity and specificity 13,14 . Once the instrument was applied, the scores obtained for each question in EAT-26 are added up and computed for each person evaluated.…”
Section: Artigo Originalmentioning
confidence: 54%
“…In the present study, the cut-off was 21 points, for this presents highly satisfactory sensitivity and specificity 13,14 . Once the instrument was applied, the scores obtained for each question in EAT-26 are added up and computed for each person evaluated.…”
Section: Artigo Originalmentioning
confidence: 54%
“…Typical results are those of Mann et al (14) who found that a threshold of 20 (on the EAT-26) yielded 88% sensitivity and 96% specificity.…”
Section: Introductionmentioning
confidence: 60%
“…The validity studies were conducted on samples of populations considered to be at higher risk for eating disorders, in which the possibility to detect disease cases was elevated (9)(10)(11)(12)14,16). This could consequently yield a higher positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations